Global warming awareness among the University of Bahrain science students - Hussain,T. (2020)
This study was designed to investigate the awareness regarding global warming among the College of Science students at University of Bahrain. A total of 143 science students were examined using a questionnaire that covered three aspects of global warming including causes, impacts, and solutions. The study included 51, 28, 40 and 24 students from the departments of biology, chemistry, mathematics, and physics respectively. The results have shown that 55 ± 10.18% of all students examined answered the questions correctly of which 51 ± 10.28% were in the first year, while 60 ± 7.4% were in their fourth year indicating a direct positive impact of university education. A significant dependence (p ⩽ 0.05) was recorded between first and fourth year students’ answers. The results have shown that fourth year biology students were the most knowledgeable, a fact that can be attributed to their academic curriculum. Therefore, the study has recommended integrating environmental concepts into the university curriculum for all students irrespective of their academic specialization in order to increase the environmental awareness.